(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
This study aims to assess the experience of the Jordan Radio and Television Corporation in implementing the Over-the-Top (OTT) Digital Platform project. It focuses on the views of the staff involved in the project regarding the stages of implementation, training, the efficiency of the digital systems used, the work environment, the challenges encountered, and the level of coordination among departments. The study also evaluates the impact of the project on the development of the professional performance and examines the role of the partnership with Jordan Media City in strengthening the technical and organizational infrastructure. This study adopted the descriptive-analytical approach by collecting data using an online questionnaire based on a five-point Likert Scale, in addition to semi-structured interviews. Data were collected during the period extending from May to August 2025. There were 27 participants, all of whom worked in the relevant sections; 70.4% were male and 29.6% were female. Moreover, (70.4%) of the sample held bachelor’s degrees, and (66.7%) of them worked in the e-platform/digital and digital media (social media) section. The Cronbach’s alpha coefficient for all areas exceeded 0.70, which indicates the validity and reliability of the measure used. The data obtained from the semi-structured interviews data was also analyzed using thematic analysis. The research findings indicated that the majority of participants expressed a positive evaluation of the digital platform project. Between 59.3% and 74.1% reported that the project was implemented in a clear and organized manner. Regarding technical support and training, between 63% and 77.8% reported receiving appropriate training that helped them perform their tasks, while 66.6% indicated a need for additional training on systems such as V-Mix and ER-Stream. Furthermore, 77.8% of participants reported that the use of digital systems such as CMS, VMS, and Catch-up helped organize work. The study concluded that the digital platform project at the Jordan Radio and Television Corporation was a successful and positive experience in terms of software and digital systems, the organization of the work environment, and the development of employees’ technical and professional skills. However, significant challenges remain at both the technical and manpower levels. This necessitates the adoption of a comprehensive digital strategy to ensure the sustainability of the platform and to further develop services such as VOD, Smart TV, and Fast TV. Such efforts will help preserve Jordan’s media heritage and enhance the corporation’s presence in digital media.